LAJU PERTUMBUHAN IKAN KERAPU (SERRANIDAE) DAN KONDISI PERAIRAN TELUK KODEK, DESA MALAKA LOMBOK BARAT - Langkosono, Langkosono (Research Center for Biology-Indonesian Institute of Sciences, 2006)
The observation of growth rate of flowery cod, Epinephelus fuscoguttatus, estuary grouper, E. tauvina and water conditions was carried out from December 2004 to June 2005, at the coastal waters of Kodek Bay, Malaka Village, West Lombok, West Nusa Tenggara Province (NTB). Early total weight of grouper fishes were 26.24 kg; at the end of study, it reaches 83.58 kg. The results shows that no significant difference on the growth rate groupers due to time of observation; while there is a significant difference on the gaining of body weight. The water conditions of surface layer and the 12 m depth, as well as temperature varied between 28.0-30.0 Â° C, salinity between 30-35 %o, dissolved oxygen between 6.1-7.0 ml/I, transparancy between 3-12 m, current velocity between 0.014-0.071 m/sec; the pH between 8.2-8.7 and air temperature 26.5-27Â°C.The nutrient phosphate varied between 0.089-0.180 /ig.at/1, nitrite between 3.112-6.032 /ig.at/1. The of aspects of growth rate of flowery cod, estuary grouper and water conditions at the culture site are discussed.